Prognostic factors of early outcome and discharge status in patients undergoing surgical intervention following traumatic intracranial hemorrhage. (September 2016) - Fujii, Tatsuhiro; Moriel, Gabriela; Kramer, Daniel R.; Attenello, Frank; Zada, Gabriel
Highlights: Prognosticators of outcome after evacuation of traumatic intracranial hematomas were examined. Younger age and higher initial GCS were associated with favorable outcomes. Absence of fever and hypernatremia were associated with favorable outcomes. Greater midline shift and coagulopathies were associated with unfavorable outcomes. Abstract: Over the past several decades, the rate of traumatic brain injury (TBI)-related emergency room visits in the United States has steadily increased, yet mortality in these patients has decreased. This improvement in outcome is largely due to advances in prehospital care, intensive care unit management, and the effectiveness of neurosurgical procedures, such as decompressive craniectomies. It is imperative to identify clinical factors predictive of patients who benefit from early mobilization of resources and operative treatment. Equally important is the identification of patients with good prognostic signs among patients receiving surgical intervention for TBI. We conducted a retrospective chart review of 181 patients requiring craniectomies and craniotomies for decompression or evacuation of an intracranial hemorrhage following TBI at a single level I trauma center between 2008-2010. Demographic features and perioperative clinical characteristics of these patients were examined in relation to favorable outcomes, defined as discharge to home or a rehabilitation facility, and unfavorable outcomes, defined as in-hospital mortality or discharge to step-down medical facilities. Younger age, greater Glasgow Coma Scale (GCS) score on admission, absence of preoperative coagulopathies, absence of hypernatremia, and absence of fever were all independent predictors of favorable outcome. Additionally, increased operative duration and increased length of hospital stay were identified as independent predictors of negative outcomes after surgery. This work supports some of the current prognostic models in the literature and identifies additional clinical variables with predictive value of early outcome and discharge status in patients undergoing surgical evacuation of traumatic intracranial hemorrhages.